Intranasal Mitochondrial Transplantation Restores Mitochondrial Function and Modulates Glial–Neuronal Interactions in a Genetic Parkinson’s Disease Model of UQCRC1 Mutation - Jui-Chih Chang; Chin-Hsien Lin; Cheng-Yi Yeh; Mei-Fang Cheng; Yi-Chieh Chen; Chi-Han Wu; Hui-Ju Chang; Chin-San Liu (Cells)
The intranasal delivery of exogenous mitochondria is a potential therapy for Parkinson’s disease (PD). The regulatory mechanisms and effectiveness in genetic models remains uncertain, as well as the impact of modulating the mitochondrial permeability transition pore (mPTP) in grafts. Utilizing UQCRC1 (p.Tyr314Ser) knock-in mice, and a cellular model, this study validated the transplantation of mitochondria with or without cyclosporin A (CsA) preloading as a method to treat mitochondrial dysfunction and improve disease progression through intranasal delivery. Liver-derived mitochondria were labeled with bromodeoxyuridine (BrdU), incubated with CsA to inhibit mPTP opening, and were administered weekly via the nasal route to 6-month-old mice for six months. Both treatment groups showed significant locomotor improvements in open-field tests. PET imaging showed increased striatal tracer uptake, indicating enhanced dopamine synthesis capacity. The immunohistochemical analysis revealed increased neuron survival in the dentate gyrus, a higher number of tyrosine hydroxylase (TH)-positive neurons in the substantia nigra (SN) and striatum (ST), and a thicker granule cell layer. In SN neurons, the function of mitochondrial complex III was reinstated. Additionally, the CsA-accumulated mitochondria reduced more proinflammatory cytokine levels, yet their therapeutic effectiveness was similar to that of unmodified mitochondria. External mitochondria were detected in multiple brain areas through BrdU tracking, showing a 3.6-fold increase in the ST compared to the SN. In the ST, about 47% of TH-positive neurons incorporated exogenous mitochondria compared to 8% in the SN. Notably, GFAP-labeled striatal astrocytes (ASTs) also displayed external mitochondria, while MBP-labeled striatal oligodendrocytes (OLs) did not. On the other hand, fewer ASTs and increased OLs were noted, along with lower S100β levels, indicating reduced reactive gliosis and a more supportive environment for OLs. Intranasally, mitochondrial transplantation showed neuroprotective effects in genetic PD, validating a noninvasive therapeutic approach. This supports mitochondrial recovery and is linked to anti-inflammatory responses and glial modulation.